1997
DOI: 10.3168/jds.s0022-0302(97)76074-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Fermentation Acid Production in the Rumen and the Requirement for Physically Effective Fiber

Abstract: The content of ruminally fermented OM in the diet affects the fiber requirement of dairy cattle. Physically effective fiber is the fraction of feed that stimulates chewing activity. Chewing, in turn, stimulates saliva secretion. Bicarbonate and phosphate buffers in saliva neutralize acids produced by fermentation of OM in the rumen. The balance between the production of fermentation acid and buffer secretion is a major determinant of ruminal pH. Low ruminal pH may decrease DMI, fiber digestibility, and microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
509
8
62

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 670 publications
(623 citation statements)
references
References 89 publications
27
509
8
62
Order By: Relevance
“…Accordingly, large particles are believed not to be immediately available for passage from the rumen, having a greater ability to stimulate chewing activity in addition to the chemical composition of feeds. Increasing forage particle length increases chewing time (Kononoff and Heinrichs, 2003;Yang and Beauchemin, 2006), which stimulates saliva secretion (Allen, 1997) in lactating cows. Beauchemin et al (2008) observed that greater proportions of forage dry matter (DM), NDF and longer particle length in a Present address: Novus International, Inc., 20 Research park Drive, St. Charles, MO 63304, USA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, large particles are believed not to be immediately available for passage from the rumen, having a greater ability to stimulate chewing activity in addition to the chemical composition of feeds. Increasing forage particle length increases chewing time (Kononoff and Heinrichs, 2003;Yang and Beauchemin, 2006), which stimulates saliva secretion (Allen, 1997) in lactating cows. Beauchemin et al (2008) observed that greater proportions of forage dry matter (DM), NDF and longer particle length in a Present address: Novus International, Inc., 20 Research park Drive, St. Charles, MO 63304, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Nasrollahi et al (2012) observed an increase in TC time for greater particle length and no differences in ruminating. However, comparisons of the current results to these experiments should take into consideration differences between experiments that affect chewing behavior: F : C (De Boever et al, 1990;Tafaj et al, 2005), cows' physiological stage (De Boever et al, 1990), level of feed intake (De Boever et al, 1990;Beauchemin, 1991), forage quality (Welch and Smith, 1970;Zebeli et al, 2012), feeding method (Maekawa et al, 2002) and rumen fermentability of the diet (Allen, 1997;Nasrollahi et al, 2012;Zebeli et al, 2012). To reduce particle length of forage, cows can either increase time spent eating and ruminating, increase rate of chewing or both (Yang and Beauchemin, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, saliva production is the main source of bicarbonate in the rumen environment (Erdman, 1988). Thus, eating and ruminating activities are important components of the digestive function because they are associated with increased saliva output (Bailey and Balch, 1961;Allen, 1997). The amount of daily BICARB secretion through saliva is greater than that entering the rumen through dietary buffers (Erdman, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…However, other management factors may alter the eating patterns and become the cause of low ruminal pH, e.g. factors that increase meal size and eating rate may result in lower ruminal pH and greater risk of acidosis (Allen, 1997;Owens et al, 1998;Schwartzkopf-Genswein et al, 2003). Feeding BICARB increased ruminal pH and osmolality (Rogers and Davis, 1982).…”
Section: Introductionmentioning
confidence: 99%